The role of PRX1-expressing cells in periodontal regeneration and wound healing - Huang, Zhen; Su, Xu; Julaiti, Miliya; Chen, Xiaotao; Luan, Qingxian (Frontiers in Physiology, 2023)
The ideal outcome of wound healing is the complete restoration of the structure and function of the original tissue. Stem cells are one of the key factors in this process. Currently, the strategy of periodontal regeneration based on mesenchymal stem cells (MSCs) is generally used to expand stem cells in vitro and then transplant them in vivo. However, their clinical application is limited. In fact, the human body has the capacity to regenerate through stem cells residing in different tissues, even without external therapeutic intervention. Stem cell niches are present in many adult tissues, such as the periodontal ligament and gingiva, and stem cells might remain in a quiescent state in their niches until they are activated in response to a regenerative need. Activated stem cells can exit the niche and proliferate, self-renew, and differentiate to regenerate original structures. Thus, harnessing the regenerative potential of endogenous stem cells in situ has gained increasing attention as a simpler, safer, and more applicable alternative to stem cell transplantation. Nevertheless, there are several key problems to be solved in the application of periodontal MSCs. Thus, animal studies will be especially important to deepen our knowledge of the in vivo mechanisms of MSCs. Studies with conditional knockout mice, in which the expression of different proteins can be eliminated in a tissue-specific manner, are especially important. Post-natal cells expressing the paired-related homeobox protein 1 (PRX1 or PRRX1), a transcription factor expressed in the mesenchyme during craniofacial and limb development, have been shown to have characteristics of skeletal stem cells. Additionally, following wounding, dermal Prx1+ cells are found out of their dermal niches and contribute to subcutaneous tissue repair. Postnatal Prx1+ cells are uniquely injury-responsive. Meanwhile, current evidence shows that Prx1+ cells contribute to promote dentin formation, wound healing of alveolar bone and formation of mouse molar and PDL. Initial result of our research group also indicates Prx1-expressing cells in bone tissue around the punch wound area of gingiva increased gradually. Collectively, this review supports the future use of PRX1 cells to stimulate their potential to play an important role in endogenous regeneration during periodontal therapy.